The Provision of Public Street Lighting Based on Risk Mitigation for Energy Efficiency and Environmental Protection - Yuki Mahardhito Adhitya Wardhana (IKIP Mataram, 2024)
Public Street Lighting (PSL) is part of road infrastructure that is vital for the safety and comfort of road users. The availability of PSL can also boost the economic growth of a municipality because the longevity of activities from the population and the industry is increased. The crucial role of PSL is still not being offset with good availability and management most municipalities in Indonesia still cannot fulfill the needs of good PSL requirements and using a lot of electricity. This is due to the lack of PSL management in Indonesia is caused by the limitations of technical aspect management and lack of technological availability, limitations of the administrative function as well as lack of alternative financing scheme. To accelerate the availability of PSL and to optimize the management it needs an efficient provision scheme and mitigate risk caused by the ineffective management of PSL. The methodology that is being used in this research are problem solver and risk sharing approaches. The result of this research shows that compared to conventional procurement from the state budget, the Public Private Partnership (PPP) scheme can solve most of the provision and management problems of PSL. In the PPP scheme, there is a risk transfer of 80% from the government to the public sector so that PSL services are better, this is balanced by the positive value of Value for Money (VFM). The energy efficiency potential of the PSL PPP can reduce up to 53% of electrical energy use from replacing lamps in PSL. The use of LED lights makes waste from PSL more environmentally friendly because it does not contain mercury like traditional lamps which are widely used in PSL and reduces CO2 emissions produced by electrical energy.The Government must promote the PPP scheme as part of innovative financing for the provision and management of PSL in Indonesia as there are only 3 out of 514 municipalities that has already implemented the PPP scheme for PSL Project.